2013
DOI: 10.14257/ijmue.2013.8.5.26
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Sharing Model for Coexistence between High Altitude Platform System and Fixed Services at 5.8 GHz

Abstract: This paper sheds the light on coexistence and sharing between high altitude platform system (HAPS) and Fixed Services (FS) as a recently critical issue due to the spectrum shortage. International Telecommunications Union Radiocommunications sector (ITU-R) allocated the 5850-7075 MHz band for the operation of HAPS along with existing FS services. Therefore, coexistence and sharing requirements like separation distance and frequency separation coordination must be achieved in terms of both co-channel and adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Alexandre et al [10] studied the coexistence of HAP with point-to-point Fixed Service (FS) in adjacent channels on 2 GHz frequency band and showed that the Interference to Noise Ratio (INR) of HAP to FS is smaller than the given threshold of protection criterion. Mokayef et al [11] studied the spectrum sharing at 5.8 GHz, and the results show that the large channel bandwidth and the existence of guard band are beneficial to the coexistence of HAP and FS. Konishi et al [12] proposed a spectrum sharing scheme based on carrier aggregation.…”
Section: ) Traffic Offloading For Mobile Communication Systemsmentioning
confidence: 99%
“…Alexandre et al [10] studied the coexistence of HAP with point-to-point Fixed Service (FS) in adjacent channels on 2 GHz frequency band and showed that the Interference to Noise Ratio (INR) of HAP to FS is smaller than the given threshold of protection criterion. Mokayef et al [11] studied the spectrum sharing at 5.8 GHz, and the results show that the large channel bandwidth and the existence of guard band are beneficial to the coexistence of HAP and FS. Konishi et al [12] proposed a spectrum sharing scheme based on carrier aggregation.…”
Section: ) Traffic Offloading For Mobile Communication Systemsmentioning
confidence: 99%
“…The authors also suggest that appropriately exploiting power control of the terrestrial system can allow for the accommodation of more interference from the newly activated HAP system. Similar underlying ideas presented in [16], [92], [93], propose the implementation of an appropriate separation distance between the systems and antenna beam adjustment, as strategies that can be adopted to improve performance and ensure coexistence of the systems.…”
Section: Hap-terrestrial Systems Coexistencementioning
confidence: 99%
“…A summary of the power control schemes reported in the HAPS literature is provided in Table IV. HAPS Placement and Constellation Optimization [175][176][177] Channel/Subchannel Allocation and Spectrum Sharing [164][165][166][167][168][169][170][171][172][173][174] Mobility and Power Control [156], [160][161] Power Control for Multicast Services [95], [98], [106][107][108] Joint Radio and Computational Power Management [163] Joint Power, Subchannel and Time Allocation [168][169][170] Spectrum Management and Sharing [171][172][173][174] Antenna and Interference Management [142, 143] [178-191] Exploiting Coordinated Multipoint Transmission and Platform Diversity [142], [185][186][187] Adaptive Cell Shaping [143], [178][179][180][181][182][183][184] Massive MIMO for HAPS Systems…”
Section: A Power Control/allocation and Interference Management In Ha...mentioning
confidence: 99%
“…The impact of the antenna beamwidths and adaptive modulation are considered. The authors in [173] investigates the co-existence of HAPS and fixed terrestrial networks in the 5850-7075 MHz band. In [174], the authors consider a spectrum sharing problem in a LEO-HAPS…”
Section: B Channel/sub-channel Allocation and Spectrum Sharingmentioning
confidence: 99%